Ritual Practice at Late Iron-Age and Viking-Age Cemeteries in Norway: The Mortuary Houses From Skeiet, Vinjeøra. - Sauvage, Raymond; Macphail, Richard I. (Medieval Archaeology, 2024)
THREE PROPOSED LATE IRON- AND VIKING-AGE MORTUARY HOUSES were recently excavated in Central Norway. Excavations and geoarchaeological investigations imply underground wooden buildings resembling domestic houses with doors. Radiocarbon dating indicates three succeeding buildings dating c AD 500–950. The finds included animal and food sacrifices. With their funerary context, the buildings provided an opportunity to frequently visit and interact with mortuary remains, as part of the rituals practised at cemeteries. They provided a ritualised space between the living and their dead relations.